Decentralization Of Information Using Blockchain Technology On Mobile Apps E-Journal - Agung Rizky; Lutfiani, Ninda; Sri Mariyati, Wayan; Atika Sari, Apriani; Febrianto, Kurnia Rizky (IAIC Bangun Bangsa, 2022)
Decentralization is the division of centralized power processes as a whole into separate ones. Blockchain technology is a basic technology that enables decentralization and gives all users the opportunity to become part of the validator or node for future transactions. The purpose of this research is to develop and develop a tamper-resistant E-Journal Mobile Application system using Blockchain Technology, which supports reliable and auditable computing using a decentralized network, not only that, this research can also develop and develop an E-Journal Application System. Cellular that is resistant to interference from hackers or system crashes. By using Blockchain technology, it can solve problems that are reliable and can be done and controlled using a decentralized network. with great hope that choosing this type of decentralized blockchain technology will be useful in preventing errors and errors in the system. This is one of the main strengths of Blockchain Technology. With this decentralized transaction log, it will not be easy and it is impossible for a database consisting of hundreds to thousands of computers to be hacked or tampered with easily. This research is a model that can be implemented as a Blockchain technology development on Mobile Apps E-journals. In this study will be made using 3 methods, namely the data analysis method, the analysis method using SWOT and the development method using a waterfall with a combination of the three methods will make this research more effective and efficient.